Students' Perception on Group Work Activity at The Tenth Grade English Class of SMAN 10 Padang - Cici Afriyani; Carbiriena Solusia (Journal of English Language Teaching, 2022)
Group work activity is one of the common learning methods that the teacher uses to engage students in the teaching and learning process. This study aimed to determine the students’ perception of group work activity in English class. Descriptive quantitative research was employed in this study. The tenth-grade students were the population of this research. There were 72 students selected as the sample through the purposive sampling method. Data were collected through a questionnaire including 4 indicators and semi-structured interviews. The collected data were analyzed using the descriptive technique. Findings revealed that students had a positive perception toward the implementation of group work activity in English class. They agree that group work could motivate them to be more active in the learning process and increase their speaking skill. It was also found that students felt more confident to speak English in groups rather than individually. Moreover, they did not find a very significant problem that hindered the implementation of group work activity in English class.